2003
DOI: 10.1177/10883576030180030601
|View full text |Cite
|
Sign up to set email alerts
|

Developing Legally Correct and Educationally Appropriate Programs for Students With Autism Spectrum Disorders

Abstract: Over the past decade, there has been a dramatic increase in litigation regarding the education of students With autism spectrum disorders (ASD). Because of the complexity of ASD and the costs of litigation related to the Individuals With Disabilities Education Act, ASD has become a high-stakes issue for parents and school districts. The purpose of this article is to extrapolate principles from the ASD litigation to provide guidelines to assist Individualized Education Program teams in developing appropriate sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 8 publications
0
46
0
2
Order By: Relevance
“…While the other components of IDEA-appropriate evaluation, parent and student participation, and procedural safeguards-have also been the source of litigation among families of children with ASD (e.g., Zirkel 2002), the majority of cases relate to services, particularly the provision of appropriate services, which is required by law, as opposed to provision of optimal services, which is not (Mandlawitz 2002). What constitutes the least restrictive environment also has been litigated frequently (Yell et al 2003). Furthermore, between 1997 and 2002, more than half the disputes related to appropriate IEPs for children with ASD involved families of preschoolers (Etscheidt 2003), suggesting that parents of preschoolers with ASD are either a particularly litigious or a particularly dissatisfied group (or both).…”
Section: Introductionmentioning
confidence: 97%
“…While the other components of IDEA-appropriate evaluation, parent and student participation, and procedural safeguards-have also been the source of litigation among families of children with ASD (e.g., Zirkel 2002), the majority of cases relate to services, particularly the provision of appropriate services, which is required by law, as opposed to provision of optimal services, which is not (Mandlawitz 2002). What constitutes the least restrictive environment also has been litigated frequently (Yell et al 2003). Furthermore, between 1997 and 2002, more than half the disputes related to appropriate IEPs for children with ASD involved families of preschoolers (Etscheidt 2003), suggesting that parents of preschoolers with ASD are either a particularly litigious or a particularly dissatisfied group (or both).…”
Section: Introductionmentioning
confidence: 97%
“…These findings make a significant contribution to the almost nonexistent social validation research in the field of autism, and provide guidelines for establishing and maintaining effective autism programs. The social validation of promising special education practices for use in autism classrooms is an especially timely and important outcome, as teachers, administrators, and parents seek to comply with Federal mandates to identify and implement research-demonstrated interventions and practices (Yell et al 2003(Yell et al , 2005. Importantly, the major consumers of autism programming (parents, teachers, and administrators) demonstrated a surprisingly high and consistent level of agreement on ratings of the importance of the specific interventions rated on the survey.…”
Section: Discussionmentioning
confidence: 94%
“…Worse, they may continue to implement unproven or less effective strategies. In addition, the existing lack of agreement between many parents and school personnel about what constitutes appropriate programming in autism classrooms (Arick et al 2005;Yell et al 2003) could continue to impede successful collaboration. Without research clearly identifying empirically and socially valid practices in autism, the progress and outcomes of students with autism on important school, home, and community goals, and ultimately, their overall quality of life, will continue to be severely and negatively impacted.…”
mentioning
confidence: 98%
“…This is a particular concern for children with special needs to also have access to their future education. Working with children with special needs is full of challenges (Robertson, Chamberlain, & Kasari, 2003;Yell, Katsiyannis, Drasgow & Herbst, 2003) and demands patience, empathy, and acceptance. The task of helping students with special educational needs (SEN) is often confronted with unpredictable situations such as suddenly students go berserk, oppose, have tantrums, or even become aggressive and attack the teachers while the teachers must withhold their negative emotions (Hochschild, 2012;Johnson et al, 2005;Stansfeld, Rasul, Head, & Singleton, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the efforts that can be done to help maintain and improve the mental health of the teachers for students with special needs is by providing effective training (Yell, Drasgow, & Lowrey, 2005;Yell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%